Defensive Gun Uses: New Evidence from a National Survey - Cook, Philip J. (Journal of quantitative criminology, 1998)
The number of civilian defensive gun uses (DGUs) against criminal attackers is regularly invoked in public policy debates as a benefit of widespread private ownership of firearms. Yet there is considerable uncertainty for the prevalence of civilian DGUs, with estimates ranging from 108,000 (using the National Crime Victimization Survey) to 2.5 million (using smaller telephone surveys) per year. In this paper we analyze the results of a new national random-digit-dial telephone survey to estimate the prevalence of DGU and then discuss the plausibility of the results in light of other well-known facts and possible sources of bias in survey data for sensitive behaviors. Because DGU is a relatively rare event by any measure, a small proportion of respondents who falsely report a gun use can produce substantial overestimates of the prevalence of DGU, even if every true defensive gun user conceals his or her use. We find that estimates from this new survey are apparently subject to a large positive bias, which calls into question the accuracy of DGU estimates based on data from general-population surveys. Our analysis also suggests that available survey data are not able to determine whether reported DGU incidents, even if true, add to or detract from public health and safety.